ANALISIS PENGUASAAN KATAGANTI “MEI”DAN “GE”PADA MAHASISWA ANGKATAN 2017 PENDIDIKAN BAHASA MANDARIN - Annisa Miftahul Khusna; Ina Ina; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractPronoun is important part of Chinese grammar. Pronoun is words with substitution and person. There are many pronouns in Chinese, which is "mei" and "ge". Although both of them are demonstrative pronouns, they have the function of demonstrative distinction and substitution. Therefore, Chinese learners are prone to make mistakes in these two words. In order to understand the mastery condition of Mandarin Education Study Program FKIP UNTAN 2017 students toward mastery of the pronoun words “mei” and “ge”, the writer used a test method to examine students understanding and the difficulties of pronoun “mei” and “ge”. The results of the study stated that the mastery of students in the prounoun “mei” was better than “ge”. The percentage of correct answers for the word “mei” is 80% and the percentage of correct answers for the word “ge” is only 60%. In this analysis of the types difficulties, the writer realized that students did not grasp well that "mei" refers to any individual in the whole, and that "ge" is used to represent the whole and "ge" mainly refers to all at the same time. Keywords: pronoun Word, mei  and ge, Condition of Mastery